Identifying knowledge transfer requirement in global organisational contexts. (1st January 2012) - Worasinchai, Lugkana; Daneshgar, Farhad
This article studies the inter-organisational (IO) knowledge transfer in global supply chains. A representative case was selected that consists of a number of laboratory analysis equipment dealer companies in Thailand and their customer companies in different industries in various parts of the world. Using the theories and frameworks in knowledge transfer in inter-organisational relationships, a survey questionnaire instrument was designed and data were collected from 73 employees of dealer companies and 87 employees of their customer companies (users of the laboratory equipment) scattered in different industries worldwide. Results indicate that the intra-organisation characteristics of the dealer companies which are expected to affect transfer of the necessary knowledge to the customers has no significant relationship with the nature of knowledge that is transferred or with the inter-organisation management. Moreover, there is no statistical significance in the intra-organisation relationships within the client companies perhaps because the majority of laboratory analysis equipment dealer companies import a great part of their products from overseas companies and they do not possess the technology themselves. Based on the findings, appropriate guidelines were provided for the enhancement of the effectiveness of the knowledge transfer process within the wide case study of this research.